2021
DOI: 10.3389/fimmu.2021.780810
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Appraisal of Literature Concerning the Analysis of Genetic Variants or Protein Levels of Complement Components on Susceptibility to Infection by Trypanosomatids: A Systematic Review

Abstract: BackgroundTrypanosomatids are protozoa responsible for a wide range of diseases, with emphasis on Chagas Disease (CD) and Leishmaniasis, which are in the list of most relevant Neglected Tropical Diseases (NTD) according to World Health Organization (WHO). During the infectious process, immune system is immediately activated, and parasites can invade nucleated cells through a broad diversity of receptors. The complement system − through classical, alternative and lectin pathways − plays a role in the first line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that Leishmania donovani is able to inhibit the lectin pathway through the activity of its Inhibitor of Serine Proteases 2 (LdISP2), preventing the formation of the MAC by reducing the formation of C3 and C5 convertases ( Verma et al., 2018 ). Finally, studies have shown that genetic modifications in complement genes, such as single nucleotide polymorphisms (SNPs), can influence host susceptibility to these parasites ( Tirado et al., 2021 ).…”
Section: Complement Systemmentioning
confidence: 99%
“…It has been shown that Leishmania donovani is able to inhibit the lectin pathway through the activity of its Inhibitor of Serine Proteases 2 (LdISP2), preventing the formation of the MAC by reducing the formation of C3 and C5 convertases ( Verma et al., 2018 ). Finally, studies have shown that genetic modifications in complement genes, such as single nucleotide polymorphisms (SNPs), can influence host susceptibility to these parasites ( Tirado et al., 2021 ).…”
Section: Complement Systemmentioning
confidence: 99%